How Specific Are Risk Factors for Headache in Adolescents? Results from a Cross-sectional Study in Germany - Lehmann, Steffi; Milde-Busch, Astrid; Straube, Andreas; von Kries, Ruediger; Heinen, Florian (Neuropediatrics, 2013)
Background The identified preventable risk factors for primary headache in adolescents are smoking; consumption of coffee or alcoholic mixed drinks; physical inactivity; muscle pain in the head, neck, or shoulder region; and chronic stress.Objective To investigate the interrelation of headache with other health complaints and the specificity of the above-mentioned risk factors for headache in adolescents.Methods A total of 1,260 students (grades 10 and 11) filled in questionnaires on headache, dietary, and lifestyle factors. The type of headache and health complaints such as dizziness, abdominal pain, musculoskeletal pains, symptoms of possible fatigue syndrome, and psychic complaints were assessed.Results Isolated headache was found in 18% of the headache sufferers; most frequently isolated tension-type headache (78.2%). Only among adolescents with a combination of headache (mainly migraine) and other health complaints, significant associations for almost all analyzed risk factors were found. The strength of the associations with the considered risk factors was very similar in all three analyzed strata except for considerably lower odds ratios for isolated headache.Conclusion All analyzed risk factors are nonspecific for headache in adolescents because they also increase the risk for other health complaints. Interventions, therefore, should consider a holistic approach focusing not only on headache but also on a broader spectrum of health complaints.
Keywords: isolated headache; adolescents; pain; health complaints; risk factors; specificity